2002
DOI: 10.1038/nature711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the learning deficits in a mouse model of neurofibromatosis type 1

Abstract: Neurofibromatosis type I (NF1) is one of the most common single-gene disorders that causes learning deficits in humans. Mice carrying a heterozygous null mutation of the Nfl gene (Nfl(+/-) show important features of the learning deficits associated with NF1 (ref. 2). Although neurofibromin has several known properties and functions, including Ras GTPase-activating protein activity, adenylyl cyclase modulation and microtubule binding, it is unclear which of these are essential for learning in mice and humans. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
546
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(580 citation statements)
references
References 28 publications
30
546
2
2
Order By: Relevance
“…27 Interestingly, the learning deficits in an animal model of neurofibromatosis type I have recently been attributed to deficits in LTP, resulting from increased GABA-mediated inhibition. 28 Moreover, as the LTP and learning deficits were reversed by GABA antagonist, the impairment is not likely to be attributable to neurotoxicity. This finding is again compatible with our observation of association between higher activity SSADH alleles (which are expected to reduce GABA) and higher general intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…27 Interestingly, the learning deficits in an animal model of neurofibromatosis type I have recently been attributed to deficits in LTP, resulting from increased GABA-mediated inhibition. 28 Moreover, as the LTP and learning deficits were reversed by GABA antagonist, the impairment is not likely to be attributable to neurotoxicity. This finding is again compatible with our observation of association between higher activity SSADH alleles (which are expected to reduce GABA) and higher general intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies in mice that are heterozygous for the Nf1 mutation, suggest that cognitive impairment in Nf1 is linked with excessive RAS activity and increased GABA inhibition in the hippocampus. 45 Furthermore, the learning problems and the GABA inhibition are reversed by a reduction in RAS, implying that farnesyl transferase inhibitor drugs might play a therapeutic role in cognitive impairment in Nf1. 45 The cholesterol lowering drug Lovastatin inhibits p21 RAS /mitogen activated protein kinase and a recent study demonstrated that the drug reverses learning and attention deficits in a mouse model of Nf1.…”
Section: Cognitionmentioning
confidence: 99%
“…45 Furthermore, the learning problems and the GABA inhibition are reversed by a reduction in RAS, implying that farnesyl transferase inhibitor drugs might play a therapeutic role in cognitive impairment in Nf1. 45 The cholesterol lowering drug Lovastatin inhibits p21 RAS /mitogen activated protein kinase and a recent study demonstrated that the drug reverses learning and attention deficits in a mouse model of Nf1. 46 Currently, Lovostatin is being investigated as a potential treatment for cognitive impairment in children with Nf1.…”
Section: Cognitionmentioning
confidence: 99%
“…In particular, great interest has developed with regard to interventions that might improve cognition, learning, and memory in the RASopathies (Shilyansky et al 2010b). Studies involving animal models of NF1 (e.g., Costa et al 2002) have led to the first clinical trials that target abnormal Ras signaling using statin drugs. Phase 1 trials indicate that these drugs can be safely prescribed in children with NF1, and there is some evidence that the drug lovastatin could affect specific cognitive outcomes (Acosta et al 2011).…”
Section: Directions For Future Researchmentioning
confidence: 99%